Molecular identification of Cyclosorus parasiticus (L.) Farw. From Gumitir, Jember Indonesia - Rizqoni, Moh Ikmal Alfi; Setyati, Dwi; Su'udi, Mukhamad; Ulum, Fuad Bahrul; Dwinianti, Edia Fitri (BIOEDUKASI, 2024)
Cyclosorus parasiticus (L.) Farw. from Mount Gumitir dominates the understory ferns vegetation along the roadside of a pine-mixed coffee plantation. Previous studies reported the metabolite profile with the flavonoid and alkaloid content. Current observations based on morphological structure of the specimens collection indicated a high variations, therefor molecular identification was required to support the phylogenetic data of the species. The aim of the study was to identify the Cyclosorus parasiticus sample originate from Gumitir using DNA barcode. We used three primers, i.e. ribulose 1,5-biphosphate carboxylase (rbcL), maturase K (matK), and Internal transcribed spacer 2 (ITS2) for molecular identification. The result showed that Cyclosorus parasiticus from Gumitir has a highest similarity with Christella latipinna (NC070300) from China with a value of Percent Identities value of 99.11% based on the ITS2 marker. The rbcL data in this study might contribute to supporting the molecular genus concept from recent Thelypteridaceae phylogeny.